SECURING SEARCH SYSTEMS: AN END-TO-END ENCRYPTION FRAMEWORK FOR PRIVACY PRESERVATION - Muskaan Mongia (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Modern search engines now face great difficulty in securing personally identifiable information (PII) given the exponential expansion in digital data processing and growing privacy protection issues. This article offers a complete architectural framework using encryption at every level of search infrastructure, therefore providing a creative method of privacy protection without compromising system performance. There are seven linked security elements in the framework that cooperate to provide unbreakable protection against privacy violations. Client-side encryption guarantees that searches are secured before transmission at the user interface level; Transport Layer Security (TLS) guarantees safe data transit across networks. Strong server-side encryption systems and particular database encryption methods for kept data help the framework to improve data safety even more. Advanced homomorphic encryption transforms privacy-preserving search capability by enabling computational activities on encrypted data. This is matched by advanced data anonymizing methods that preserve data utility while safeguarding individual privacy and complex access control systems with strict key management standards.Combining these security layers produces a strong architecture that enables companies to keep a careful equilibrium between user privacy and search capability. Through a thorough investigation, this article investigates the complex technical issues of implementation, including system performance optimization, scalability concerns, and resource economy. This article explores important facets of regulatory compliance, looking at how the structure fits changing data protection rules and handles the difficult criteria of contemporary privacy regulations. This article shows thorough performance measures and optimization techniques to show how companies could efficiently reduce the computational expense of encryption and maximize security advantages. This article also looks at user experience consequences and offers ideas on how to keep system responsiveness in the face of all-encompassing security policies. In a time when data privacy has taken the front stage, this all-encompassing approach not only improves privacy protection but also provides a basis for developing and preserving user confidence.